So similar and yet so different: A firm's net costs and post-training benefits from apprenticeship training in Austria and Switzerland. Issue 2 (8th January 2019) - Moretti, Luca; Mayerl, Martin; Muehlemann, Samuel; Schlögl, Peter; Wolter, Stefan C.
Abstract : Purpose: The purpose of this paper is to compare a firm's net cost and post-apprenticeship benefits of providing apprenticeship training in Austria and Switzerland: two countries with many similarities but some critical institutional differences. Design/methodology/approach: The authors draw on detailed workplace data with information on the costs and benefits of apprenticeship training, as well as on hiring costs for skilled workers from the external labour market. The authors use nearest-neighbour matching models to compare Austrian firms with similar Swiss firms based on observable characteristics. Findings: On average, a Swiss firm generates an annual net benefit of €3, 400 from training an apprentice, whereas a firm in Austria incurs net costs of €4, 200. The impetus for this difference is largely a higher relative apprentice pay in Austria. However, compared with Swiss firms, Austrian firms generate a higher post-training return by retaining a higher share of apprentices and savings on future hiring costs. Practical implications: The authors demonstrate that apprenticeship systems can exist under different institutional environments. For countries currently in the process of establishing or expanding apprenticeship systems, the comparative analysis clearly shows that policymakers should consider more than just one country's particular apprenticeship model. Originality/value: The authors provide a first comparative analysis between two apprenticeship countries that empirically assesses a firm's costs and benefits of training during an apprenticeship programme and also provides a monetary value of a particular type of post-training benefits that firms can generate by retaining former apprentices as skilled workers (i.e. savings in future hiring costs for skilled workers).